Privacy Protection of Node Location and Data in Wireless Sensor Networks - He, Huan (International Journal of Online and Biomedical Engineering (iJOE), 2016)
In order to solve the problem of low safety and low efficiency in distributed data protection in wireless sensor networks, a new method for privacy protection of node location and data in wireless sensor networks is researched in this paper. The author develops a novel architectural framework that observes user-specific patterns to distinguish between legitimate users and illegitimate user’s thus enhancing and strengthening user authentication. An engine that calculates the authentication score (the similarity of features of the past and recent behaviors) for a given user is proposed. Simulation results show that the proposed method can improve overall system performance substantially.